Sustained remission from perinatal depression after bright light therapy: A pilot randomised, placebo‐controlled trial. (3rd August 2022) - Garbazza, Corrado; Cirignotta, Fabio; D'Agostino, Armando; Cicolin, Alessandro; Hackethal, Sandra; Wirz‐Justice, Anna; Cajochen, Christian; Manconi, Mauro; ,
Abstract: Objective: Perinatal depression (PND) is a severe complication of pregnancy, affecting both mothers and newborns. Bright light therapy (BLT) has only been tested in a few studies for treating either antenatal or postnatal depression. We conducted a pilot trial to investigate the efficacy and safety of BLT for PND occurring at any time across the perinatal period. Methods: A single‐blind RCT was carried out in women with an EPDS >12 from the 2nd gestational trimester until 9 months postpartum. Participants received either 30‐minutes morning BLT (10′000 lux) or dim red light (DRL, 19 lux) for 6 weeks. Results: Twenty‐two women were randomised to BLT ( n  = 11) or DRL ( n  = 11). Among those receiving BLT, 73% achieved remission (improvement ≥50%, EPDS score ≤ 12), in contrast to 27% in the DRL group ( p  = 0.04). A significant influence of time on EPDS score and group‐time interaction emerged, with a greater reduction in the BLT‐group across the follow‐up period. No women in either group reported major side effects. Conclusion: Morning BLT induced a significant remission from PND as compared to DRL and this effect was maintained across the perinatal period. BLT showed an excellent safety profile and was well‐tolerated, thus representing a valid therapeutic strategy in this vulnerable perinatal population.